The Effect of Discounts, Online Customer Ratings, and Online Customer Reviews on Consumer Purchase Intention in The Shopee Marketplace - Sumiati; Irwan, Andi Muhammad; Sandira, Nur Fadilah Ayu; Rostina (Candela Edutech Indonesia, 2025)
Objectives – This study aims to examine and analyze the influence of discounts on consumer purchase intention, The influence of online customer ratings on consumer purchase intention, The influence of online customer reviews on consumer purchase intention, and The simultaneous influence of discounts, online customer ratings, and online customer reviews on consumer purchase intention on the Shopee marketplace. Methods/Approach – The sampling technique used in this study is probability sampling, specifically through the purposive sampling method. The Results - discounts (X1) have a positive and significant effect on buying interest (Y), online customer ratings (X2) have a positive and significant effect on buying interest (Y), online customer reviews (X3) have a positive and significant effect on buying interest (Y), and discounts, online customer ratings, online customer reviews simultaneously have a significant effect on purchasing interest.